GENERAL INFORMATION ABOUT AXONOMETRIC PROJECTIONS (International journal of artificial intelligence, 2026)
This article examines axonometric projections as a method for accurately and clearly representing three-dimensional objects on a plane based on the principle of parallel projection. Using this method, the spatial structure, dimensions, and shape of an object are represented simultaneously. Axonometric projections include isometric, dimetric, and trimetric types, which are widely used in technical drawing, engineering, and computer graphics.